Functional thinking and Kolb learning style: Case of solving linear and non-linear pattern problems - Muhammad Syawahid; Lalu Sucipto (Universitas Hamzanwadi, 2023)
Functional thinking (FT) is a part of algebraic thinking. Several studies revealed that algebraic thinking is influenced by learning style, and few studies showed FT viewed from learning style. This study aims to describe students’ FT views from Kolb's learning style in solving linear and non-linear pattern tasks. The study used a qualitative approach with a case study method. It involved thirty-one students in 8th grade at an Islamic State junior high school in Mataram, West Nusa Tenggara, Indonesia. Four students were selected as research subjects for analysis of answers and interviews. The Kolb learning style inventory (KLSI) collected research data, tests, and interviews. The instrument consisted of KLSI and FT tests. Data was analyzed by reduction, presenting, and verifying. The finding showed that students with convergent, divergent, and accommodator learning styles can consist of near, far, and formal generalizations and determining inverse in FT. They represented the generalization of the relationship of two quantities symbolically. Meanwhile, students with an assimilator learning style can in FT consisting of near and far generalizations in solving figural and non-figural linear pattern tasks. They can perform formal generalizations and determine inverse-solving figural and non-figural linear pattern tasks. They are also unable to solve figural non-linear pattern tasks.